2015
DOI: 10.1103/physreve.92.012715
|View full text |Cite
|
Sign up to set email alerts
|

Vesiculation of healthy and defective red blood cells

Abstract: Vesiculation of mature red blood cells (RBCs) contributes to removal of defective patches of the erythrocyte membrane. In blood disorders, which are related to defects in proteins of the RBC membrane, vesiculation of the plasma membrane is intensified. Several hypotheses have been proposed to explain RBC vesiculation but the exact underlying mechanisms and what determines the sizes of the vesicles are still not completely understood. In this work, we apply a twocomponent coarse-grained molecular dynamics (CGMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 91 publications
(138 reference statements)
1
41
0
Order By: Relevance
“…Suggested mechanisms for membrane shedding by RBCs are related to clustering of membrane proteins driving curvature generation 46,47,58 and to the balance between membrane bending and stretching of the spectrin cytoskeleton. [58][59][60] The weaker linkage of the membrane with the underlying cytoskeleton in HS likely causes loss of organization in the membrane. This is supported by the observation that diffusion of membrane proteins is faster in RBCs from patients with HS.…”
Section: Discussionmentioning
confidence: 99%
“…Suggested mechanisms for membrane shedding by RBCs are related to clustering of membrane proteins driving curvature generation 46,47,58 and to the balance between membrane bending and stretching of the spectrin cytoskeleton. [58][59][60] The weaker linkage of the membrane with the underlying cytoskeleton in HS likely causes loss of organization in the membrane. This is supported by the observation that diffusion of membrane proteins is faster in RBCs from patients with HS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been hypothesized several years ago that upon RBC aging the larger compressive forces on the cell membrane due to cytoskeleton stiffness and density increase could be accommodated by increased membrane curvature and vesicle detachment from the membrane [39,41]. Accordingly, based on a two-component coarsegrained molecular dynamics RBC membrane model, Li and Lykotrafitis have revealed that lateral compression generates large vesicles with heterogeneous composition, similar in size to the cytoskeleton corral [59]. The lower vesiculation we observed here in elliptocytosis is also in agreement with the role of the cytoskeleton, since a lower compression is expected to occur in elliptocytotic RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a two-component composite model of RBC membrane with explicit descriptions of lipid bilayer, cytoskeleton, and transmembrane proteins has been developed and implemented using coarse-grained molecular dynamics (CGMD) [10, 41, 42]. This CGMD membrane model has been successfully applied to study the membrane-related problems in RBCs such as protein diffusion and vesiculation in defective RBC membrane [43, 44], and the stiffening effects of knobs on Pf -RBCs [10]. Although changes on the biomechanics of RBC membrane, including bending rigidity and shear modulus, in certain diseases can be evaluated by modeling a small piece of cell membrane with the two-component composite model, the whole-cell characteristics strongly related to RBC biomechanics and biorheology are not efficiently depicted by modeling only a portion of the RBC membrane.…”
Section: Introductionmentioning
confidence: 99%